Socialising Government: Evaluating the Role of Social Media in Governance and Ethics in Kenya - Kamwaria, Alex N.; Kamau, John M.; Githaiga, Anne J.; Guantai, Peter M.; Mugwe, Rukahu; Makin, Kasoo R.; Dida, Golo B. (International Journal of Humanities and Social Science, 2015)
Social media involves social networking sites, such as Twitter, WhatsApp, Facebook, Skype, blogs, MySpace, YouTube, Instagram, and Weechat. Currently, social media is gaining popularity in the field of governance and ethics. Governance and ethics are matters of principled sensitivity to the rights of others. Good governance is concerned with the balance between the policies, on the one hand, and respect and responsibility to the citizens, on the other. This balance is particularly important because sound governance and sound ethics go hand in hand. This article articulates on the role of social media in promoting good governance and ethics. Since social media is relatively accessible and cheaper; it is the best and versatile publicist tool that the government can utilize to engage the public on policy and development issues. However, social media is a double-edge sword; it can build as well as destroy. As such, there is need to exercise caution in its use.
Keywords: Governance; Ethics; Social Media; Internet technology; Facebook, Twitter